2012
DOI: 10.4238/2012.january.9.2
|View full text |Cite
|
Sign up to set email alerts
|

Genetic diversity of Metrodorea nigra (Rutaceae) from a small forest remnant in Brazil assessed with microsatellite markers

Abstract: ABSTRACT. Metrodorea nigra (Rutaceae) is an endemic Brazilian tree of great ecological importance, frequently found in the submontane regions of ombrophilous dense and semideciduous forests. This tree is useful for reforesting degraded areas and the wood can be employed in construction. We developed 12 microsatellite markers from a genomic library enriched for GA/CA repeats, for this species. Polymorphisms were assessed in 40 trees of a highly fragmented population found in Cravinhos, State of São Paulo, in so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
0
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 15 publications
2
12
0
3
Order By: Relevance
“…N A = number of alleles; N E = effective number of alleles; H O = observed heterozygosity; H E = expected heterozygosity; F = fixation index; P.Ex1 = probability of exclusion for the first parental individual; P.Ex2 = probability of exclusion for the second parental individual; NAF = null alleles frequency. *Primers from Guidugli et al (2012). **Unpublished.…”
Section: Issr Markersmentioning
confidence: 99%
See 3 more Smart Citations
“…N A = number of alleles; N E = effective number of alleles; H O = observed heterozygosity; H E = expected heterozygosity; F = fixation index; P.Ex1 = probability of exclusion for the first parental individual; P.Ex2 = probability of exclusion for the second parental individual; NAF = null alleles frequency. *Primers from Guidugli et al (2012). **Unpublished.…”
Section: Issr Markersmentioning
confidence: 99%
“…Five microsatellite (SSR) primer pairs (Mtn 1, Mtn 3, Mtn 13, Mtn 16, and Mtn 19) previously developed by Guidugli et al (2012) were used in this study. To increase the number of SSR primers available for analysis, a new set of primers was designed according to the protocol described by Guidugli et al (2012), and 2 newly developed and highly polymorphic SSR primer pairs were obtained (Mtn 87 and Mtn 95,unpublished).…”
Section: Dna Extraction and Issr/ssr Amplificationmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, Müller et al (1995) isolated several compounds from its stems and leaves; Souza et al (2004) studied its flower and fruit anatomy; Pombal and Morellato (2000) investigated the correlation between its floral traits (color and odor) and main pollinators, as compared to M. stipularis; and recent works by Guidugli et al (2012) and Schwarcz et al (2010) have been focused on its genetic diversity and structure, and its mating system. In addition, many studies have reported M. nigra as a frequent species in floristic surveys (Durigan et al, 2000;Toniato and OliveiraFilho, 2004;Santos et al, 2007b), playing an important ecological role in tropical deciduous forests (Metzger, 2000), and also as a key species for forest restoration purposes in this biome (Chagas et al, 2004).…”
Section: Introductionmentioning
confidence: 99%